Training in quality improvement for the next generation of psychiatrists. (February 2017) - Ewins, Elizabeth; Macpherson, Rob; van der Linden, Geoff; Arnott, Stephen
Summary: Quality improvement (QI) projects have been shown to positively influence patient care. They provide opportunities for trainees to present and publish their work locally and nationally, and to gain valuable leadership and management experience. We describe a pilot project to engage in QI trainees across a National Health Service trust and a school of psychiatry. After the first year of this programme over half of psychiatry trainees in the school (58% of core trainees and 47% of advanced trainees) are participating in 28 individual QI projects and QI project methodology is to become embedded in the core psychiatry training course. Specialty doctors, consultants, foundation doctors, general practitioner trainees, medical students and the wider multidisciplinary team have all become engaged alongside trainees, working with patients and their families to identify problems to tackle and ideas to test.